2017
DOI: 10.1016/j.rboe.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring injuries: update article

Abstract: Hamstring (HS) muscle injuries are the most common injury in sports. They are correlated to long rehabilitations and have a great tendency to recur. The HS consist of the long head of the biceps femoris, semitendinosus, and semimembranosus. The patient's clinical presentation depends on the characteristics of the lesion, which may vary from strain to avulsions of the proximal insertion. The most recognized risk factor is a previous injury. Magnetic resonance imaging is the method of choice for the injury diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…11,29 An insufficient warm-up and a reduced muscle strength and joint range of motion are reported to be risk factors for muscle injuries. 2,6,20,29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,29 An insufficient warm-up and a reduced muscle strength and joint range of motion are reported to be risk factors for muscle injuries. 2,6,20,29…”
Section: Discussionmentioning
confidence: 99%
“…11,29 An insufficient warm-up and a reduced muscle strength and joint range of motion are reported to be risk factors for muscle injuries. 2,6,20,29 An Achilles tendon rupture is a common acute injury in tennis players 19,30 and occurs usually through a push-off mechanism, a sudden and unexpected dorsiflexion of the ankle, or a violent dorsiflexion of a plantarflexed foot. 12 Given the sudden multidirectional movement changes in tennis, unexpected ankle dorsiflexion or sudden push-off can occur abruptly.…”
Section: Discussionmentioning
confidence: 99%
“…Hamstring strain injuries (HSI) are known to be one of the most common injuries in sports. 1,2 They often result in lengthy absence from sport, ranging from a couple of weeks to several months and high recurrence rates, ranging from 12 to 33%. 1 There is a clear clinical need for either primary prevention or proper counseling to minimize the risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 They often result in lengthy absence from sport, ranging from a couple of weeks to several months and high recurrence rates, ranging from 12 to 33%. 1 There is a clear clinical need for either primary prevention or proper counseling to minimize the risk of recurrence. 3 Systematic reviews have shown that there is no strong evidence for commonly used Magnetic resonance imaging (MRI) parameters https://doi.org/10.1016/j.jsams.2021.02.008 1440-2440/© 2021 Sports Medicine Australia.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Previous studies have recorded hamstring injury prevalence ranging from 23% to 50% of muscle injuries in sports. [6][7][8] In most instances, a hamstring injury is caused by indirect trauma associated with non-contact activities that require sprinting, jumping and ballistic movements of the lower limb. 6 8 Performing these movements requires the hamstring muscle to eccentrically contract and develop tension while lengthening.…”
Section: Introductionmentioning
confidence: 99%